Предмет: Математика,
автор: Pupok2015
Найдите значение выражения: 2 3/8 * 1 4/5 - 3/5 * 2 3/8 - 1 1/5 * 3/8
Ответы
Автор ответа:
0
= 2 ( 3/8 ) * ( 1 4/5 - 3/5 ) - 1 ( 1/5 ) * 3/8 = 2 ( 3/8 ) * 1 ( 1/5 ) - 1 ( 1/5 ) * 3/8 =
= 1 ( 1/5 ) * ( 2 ( 3/8 ) - 3/8 ) = 1 ( 1/5 ) * 2 = 1,2 * 2 = 2,4
= 1 ( 1/5 ) * ( 2 ( 3/8 ) - 3/8 ) = 1 ( 1/5 ) * 2 = 1,2 * 2 = 2,4
Похожие вопросы
Предмет: Математика,
автор: malikabularova201593
Предмет: Физика,
автор: zilolamamutova
Предмет: Английский язык,
автор: Аноним
Предмет: Физика,
автор: kiramelnicova